MONITORING NOX AND TOTAL OXIDANTS FOR ENHANCED ENVIRONMENTAL SUSTAINABILITY IN ILORIN, NIGERIA - Adesanya, Abimbola Olalekan; Okonkwo, Ngozi Ifeoma; Ogunwale, Adekunle Oluwaseun (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
Urbanization has led to a pressing concern: atmospheric pollution, driven by the concentrated industrial and transportation activities in urban areas. This study focuses on the omnipresent issue of oxides of nitrogen (NOX = NO + NO2) concentrations in urban atmospheres, predominantly arising from industrial boilers and non-industrial fuel combustion, both from stationary and mobile sources. Moreover, these primary pollutants can undergo photochemical transformations, giving rise to secondary pollutants, collectively known as photochemical oxidants. Ozone stands as a prominent component of this group, along with peroxyacetylnitrate (PAN), hydrogen peroxide (H2O2), and other compounds, forming intricate multi-path photochemical processes. The production of ozone and PAN is primarily associated with the photochemical oxidation of NOX and a variety of non-methyl volatile organic compounds (NMVOC), occurring under favorable photo-dissociation conditions (Thomas et al., 1974).